Mental Health Conditions and Suicide Risk Among Costa Rican University Students - Daniel Martínez-Esquivel; Patsy Quesada-Carballo; Yerlin Quesada-Rodríguez; Ana Laura Solano-López; Derby Muñoz-Rojas (Universidad de Santander, 2024)
Introduction: University students are exposed to academic demands that could impact mental health and trigger suicidal behaviors. Objective: To analyze the mental health conditions (depression, anxiety, and social support) and suicide risk in Costa Rican university students. Materials and Methods: Correlational, predictive, and cross-sectional research was conducted. A census sample of 76 university students was included. Variables encompassed sociodemographic data, social support measured by the Multidimensional Scale of Perceived Social Support, depression measured by the Beck Depression Inventory-II, anxiety measured by the Beck Anxiety Inventory, and suicide risk measured by the Plutchik Suicide Risk Scale. An online survey was used. Descriptive analysis, variance analysis, Pearson correlation, and multiple linear regression were performed. Significance level set at p<0.05. Results: The student body had a mean age of 19.43 years ±1.75, with gender identity evenly distributed. 38.20% reported moderate-severe symptoms of depression, and 32.90% indicated suicide risk. Differences were observed between gender identity in terms of social support and anxiety (p<0.05). Correlations were found between mental health conditions and suicide risk (p=0.001). Depression was identified as a factor contributing to an increased risk of suicide (p=0.001). Discussion: Previous literature confirms that mental health conditions such as low social support, depression, and anxiety in university students would predispose to the suicide risk. Conclusions: There is a segment of the university student population experiencing adverse mental health conditions and suicide risk, for whom care strategies focused on their needs should be developed.